2008
DOI: 10.1093/brain/awn252
|View full text |Cite
|
Sign up to set email alerts
|

Resistance training in patients with single, large-scale deletions of mitochondrial DNA

Abstract: Dramatic tissue variation in mitochondrial heteroplasmy has been found to exist in patients with sporadic mitochondrial DNA (mtDNA) mutations. Despite high abundance in mature skeletal muscle, levels of the causative mutation are low or undetectable in satellite cells. The activation of these typically quiescent mitotic cells and subsequent shifting of wild-type mtDNA templates to mature muscle have been proposed as a means of restoring a more normal mitochondrial genotype and function in these patients. Becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(122 citation statements)
references
References 32 publications
2
115
0
1
Order By: Relevance
“…This result has a basis in both clinical and epidemiologic observations. Most physicians recommend exercise therapy for individuals with mitochondrial disorders (26), based on evidence of clinical benefit in mitochondrial disease (27,28) and myriad other conditions (29). The optimal exercise therapy for individuals with metabolic myopathy remains the focus of ongoing study.…”
Section: Discussionmentioning
confidence: 99%
“…This result has a basis in both clinical and epidemiologic observations. Most physicians recommend exercise therapy for individuals with mitochondrial disorders (26), based on evidence of clinical benefit in mitochondrial disease (27,28) and myriad other conditions (29). The optimal exercise therapy for individuals with metabolic myopathy remains the focus of ongoing study.…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of satellite cell-derived mitochondria explains the increase in wild-type mtDNA known as "gene-shifting. " More recently, Murphy and colleagues [139] showed that, in adults with large-scale mtDNA deletions, 12 weeks of RT induced an increase in muscle strength, myofiber damage and regeneration, NCAMpositive and COX-positive satellite cells, and oxidative capacity, supporting the RTe-induced mitochondrial gene-shifting hypothesis. Recently, Spendiff et al [140], in a study on mitochondrial DNA deletion demonstrated that in patients with mitochondrial myopathies, satellite cells presented single, large-scale mtDNA deletion/s at levels comparable with those observed in muscle.…”
Section: Exercise Training and Mitochondria ''Quality'' In The Elderlymentioning
confidence: 91%
“…Other NO-based therapeutic approaches to improve skeletal muscle performance involve diet, exercise, and pharmacological agents designed to improve mitochondrial content and OXPHOS efficiency . Aerobic training, a potent stimulus for muscle mitochondrial biogenesis, improves muscle strength and oxidative capacity in patients with mitochondrial myopathy (Murphy et al, 2008) in part through NOdependent mechanisms. An active area of research is to determine the safety, effectiveness, and the most appropriate conditioning regimens for these patients.…”
Section: A Nitric Oxidementioning
confidence: 99%